BIOLOGYOF BADIS BADIS (HAM., 1822) FROM NORTH EASTERN HILL REGION - MAHAPATRA, B. K. (Journal of the Inland Fisheries Society of India, 2021)
Badis badis or dwarf chameleon fish, also known as the blue perch or badis belongs to family Badidae of the order Perciformes. Hamilton (1822) described Labrus badis and L. dario from Gangetic provinces. Bleeker (1854) established genus Badis for L. badis under family Nandidae. Barlow et al. (1968) coined the new family, Badidae, in which Badis has been incorporated based on osteological characters. The genus is separated from the Nandid genus Nandus in having a smooth opercular margin and endentuloustoungue. As per Kullander and Britz (2002) the genus Badis is characterized by combination of the following features: Operculum with a single sharp spine at it posterior corner; spinous and soft dorsal fins continuous, the base of the soft part of the fin is longer than that of the spinous part; anal fin with three spines; lateral line pores tubed and interrupted; jaws, vomer and palatines with villiform teeth; scales both ctenoid and cycloid, 2-4 dentary formula; hypobranchial 3-toothed; males with short pelvic fin, not reaching the 1st dorsal spine; short dorsal fin lappets; rounded caudal fin (Geetakumari and Kudu, 2011). When Hamilton described this species he did so without preserving any specimens, therefore to avoid confusion with similar-looking congeners, Kullander and Britz (2002) designated a neotype, which was collected from the Tumapao River, a tributary of the Ganges located 65km north of Calcutta. B. badis commonly inhabits paddy fields, ponds and small streams and are found to be distributed in all the North Eastern States of India (Mahapatra et al., 2004).